Universalist Feminism in The Field of Authorship (A Case Study on Sidoarjo Women Writers Community) - Fediyanto, Niko; Mandarani, Vidya; Astutik, Yuli (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2020)
This research discusses the community of women writers in Sidoarjo using a feminist sociological perspective. The purpose of this research is to formulate the pattern of relations of this community with the structure of the field of authorship using Bourdieu's perspective. The research method used is qualitative with descriptive patterns. Data were collected using a combination of interview and documentation techniques using library research procedures. The results showed that this community of women writers had an awareness of the existence of dominant-dominated binary opposition structures and included aspects of gender considerations in their authorship strategies, but they chose patterns as used in universalist feminism.